Left Ventricular Dimensions and Diastolic Function Are Different in Throwers, Endurance Athletes, and Sprinters From the World Masters Athletics Championships - Hoffmann, Fabian; Moestl, Stefan; Wooten, Savannah V.; Stray-Gundersen, Sten; Tomczak, Corey R.; Tank, Jens; Tanaka, Hirofumi; Rittweger, Jörn; Chilibeck, Philip D. (Frontiers in Physiology, 2021)
There is controversy whether a lifetime of heavy resistance training, which provides pressure-overload, is harmful for left ventricular function. We compared left ventricular dimensions and function in Masters athletes involved in throwing events (requiring strength; n=21, 7 females, 60±14y) to those involved in endurance events (n=65, 25 females, 59±12y) and sprinting (n=68, 21 females, 56±13y) at the 2018 World Masters Athletic Championships. Left ventricular dimensions and function were assessed with B-mode ultrasound and Doppler. The ratio of left ventricular early diastolic peak filling velocity to peak velocity during atrial contraction (E/A) across the mitral valve and the ratio of E to velocity of the E-wave (E’) across the lateral and septal mitral annulus (E/E’) were used as indexes of left ventricular diastolic function. Intra-ventricular septal wall thickness was greater in throwers compared to sprinters (11.9±2.2 vs. 10.3±2.3 mm; p=0.01). Left ventricular end diastolic diameter relative to body surface area was higher in endurance athletes and sprinters compared to throwers (25.2±3.0, 24.3±3.1, and 22.0±3.1 mm/m2, respectively, p<0.01). The E/A was higher in endurance athletes and sprinters compared to throwers (1.35±0.40, 1.37±0.43, and 1.05±0.41, respectively; p<0.01). The E/E’ was lower in endurance athletes and sprinters compared to throwers (6.9±1.8, 6.6±1.9, and 8.1±1.9, respectively, p<0.05). When compared to age-matched historical controls (n>1,000; E/A=1.06; E/E’=7.5), left ventricular diastolic function was not different in throwers, but superior in distance runners and sprinters (p<0.01). Masters throwers have altered left ventricular dimensions and function compared to other athletes, but function appears normal and comparable to age-matched controls.